Determinants and properties of school climate and their relationships with school performance in the NJEE of catholic schools in Taiwan, ROC - Hsia, Michael Kwo Wei
The respondents consisted of 78 Catholic high school administrators, 196 teachers and 537 students. The t-test, Pearson coefficient of correlation, stepwise multiple regression analysis, analysis of variance and partial correlation were used to analyze the school climate variables and the NJEE results from 1980 to 1982. Continuous academic and social growth, program, process, and trust are the strongest positive predictors of NJEE performance while cohesiveness, material determinants, school renewal and caring are the strongest negative predictors.